Eisenmenger syndrome: JACC state-of-the-art review - Arvanitaki, Alexandra; Gatzoulis, Michael A.; Opotowsky, Alexander R.; Khairy, Paul; Dimopoulos, Konstantinos; Diller, Gerhard-Paul; Giannakoulas, George; Brida, Margarita; Griselli, Massimo; Grünig, Ekkehard; Montanaro, Claudia; Alexander, Peter David; et al. (Journal of the American College of Cardiology, 2022)
Although major breakthroughs in the field of pediatric cardiology, cardiac surgery, intervention, and overall care improved the outlook of congenital heart disease, Eisenmenger syndrome (ES) is still encountered and remains a complex clinical entity with multisystem involvement, including secondary erythrocytosis, increased thrombotic and bleeding diathesis, high arrhythmogenic risk, progressive heart failure, and premature death. Clearly, care for ES is best delivered in multidisciplinary expert centers. In this review, we discuss the considerable recent progress in understanding the complex pathophysiology of ES, means of prognostication, and improvement in clinical outcomes achieved with pulmonary arterial hypertension-targeted therapies. Additionally, we delineate areas of uncertainty in various aspects of care, discuss gaps in current evidence, and review current status in less privileged countries and propose initiatives to reduce disease burden. Finally, we propose the application of emerging technologies to enhance the delivery and quality of health care related to ES and beyond.